Plastered wall hollowing detector - CHEN WEI; TAN XIAODONG; HUANG MO; WANG BEILIN; LI JINDU; YAN KAIYANG; REN SHILU; LIU XIAOSHENG (2024)
The utility model relates to the technical field of wall hollowing detection, in particular to a plastered wall hollowing detector which comprises a first threaded rod, the circumferential outer wall of the first threaded rod is meshed with a first threaded cylinder, the circumferential outer wall of the first threaded cylinder is fixedly connected with a bent rod, and the circumferential outer wall of the bent rod is fixedly connected with a handle. The device comprises a first threaded rod, first limiting plates are fixedly connected to the outer walls of the two ends of the first threaded rod, a fixing cylinder is fixedly connected to the outer walls of the tops of one set of first limiting plates, a rotating rod is inserted into the fixing cylinder, a connecting cylinder is fixedly connected to one end of the rotating rod, and a mounting base is fixedly connected to the outer wall of one side of the connecting cylinder. According to the utility model, when a worker detects that a hollow drum is formed on